Hipotireoidismo e gestação: importância do pré-natal no diagnóstico, tratamento e acompanhamento - Lopes, Fabiana Pires Rodrigues de Almeida (Universidade Federal do Tocantins, 2017)
The research aimed to investigate the epidemiological profile of Hypothyroidism in Pregnancy in the city of Palmas-TO. This is a descriptive and exploratory study of documentary type, with quantitative approach, carried out at the Public Maternity and at the Center of Sexual and Reproductive Health. The analysis comprised 15 medical records of women with hypothyroidism, of these, eleven at the Maternity and four at the Center of Sexual and Reproductive Health (CSRH). The average maternal age was 30.2 years; the average gestational age was 16.3 years; the number of previous pregnancies was identified in 9 records; place of residence was found in 3 records and lived in urban areas; the disease personal history comprises 14 individuals; the history family in just 1 records were recorded; the history of abortions comprises 5; cases of prematurity, was not found records in medical charts; for the treatment of infertility in only 1 records noted the record; regarding the history of goiter / lump, there was obtained 2 registers; previous surgery, was not found records; hormone replacement occurred in 4 pregnant women. Regarding the repeated examinations during pregnancy, it was obtained one case in the medical records. We conclude that monitoring occurred in a timely manner with pertinent interventions; however, it is necessary to improve the quality of the medical records, since that unfilled information hindered the understanding of the prognosis of women under high risk prenatal.